Algebra
- If x2 + y2 + 6x + 5 = 4 (x – y) then (x – y) is
-
View Hint View Answer Discuss in Forum
x2 + y2 + 6x + 5 = 4x – 4y
⇒ x2 + y2 + 6x – 4x + 4y + 5 = 0
⇒ x2 + 2x + 1 + y2 + 4y + 4 = 0
⇒ (x + 1)2 + (y + 2)2 = 0
∴ x + 1 = 0 ⇒ x = –1
y + 2 = 0 ⇒ y = –2
∴ x – y = –1 + 2 = 1Correct Option: A
x2 + y2 + 6x + 5 = 4x – 4y
⇒ x2 + y2 + 6x – 4x + 4y + 5 = 0
⇒ x2 + 2x + 1 + y2 + 4y + 4 = 0
⇒ (x + 1)2 + (y + 2)2 = 0
∴ x + 1 = 0 ⇒ x = –1
y + 2 = 0 ⇒ y = –2
∴ x – y = –1 + 2 = 1
-
If x + 1 = c + 1 then the value of x is x c
-
View Hint View Answer Discuss in Forum
x + 1 = c + 1 x c ⇒ x – c = 1 – 1 c x ⇒ x – c = x – c xc ⇒ (x – c) – x – c = 0 xc ⇒ (x – c) 1 – 1 = 0 xc
⇒ x – c = 0 ⇒ x = c
or, 1 – 1 = 0 xc ⇒ 1 = 1 ⇒ xc = 1 xc ⇒ x = 1 c ⇒ x = c, 1 c Correct Option: A
x + 1 = c + 1 x c ⇒ x – c = 1 – 1 c x ⇒ x – c = x – c xc ⇒ (x – c) – x – c = 0 xc ⇒ (x – c) 1 – 1 = 0 xc
⇒ x – c = 0 ⇒ x = c
or, 1 – 1 = 0 xc ⇒ 1 = 1 ⇒ xc = 1 xc ⇒ x = 1 c ⇒ x = c, 1 c
- If p = 99, then the value of p (p2 + 3p + 3) is
-
View Hint View Answer Discuss in Forum
Expression = p (p2 + 3p + 3)
= p3 + 3p2 + 3p + 1 – 1
= (p + 1)3 – 1
= (99 + 1)3 – 1
= (100)3 – 1
= 1000000 – 1
= 999999Correct Option: B
Expression = p (p2 + 3p + 3)
= p3 + 3p2 + 3p + 1 – 1
= (p + 1)3 – 1
= (99 + 1)3 – 1
= (100)3 – 1
= 1000000 – 1
= 999999
-
If a2 + + 1 = 9a, (a ≠ 0) then the value of (a)2 + 1 is (a)2
-
View Hint View Answer Discuss in Forum
a2 + 1 = 9a
⇒ a2 + 1 = 9 a ⇒ a + 1 = 9 a
On squaring both sides,a2 + 1 + 2 = 81 a2 ⇒ a2 + 1 = 81 – 2 = 79 a2 Correct Option: C
a2 + 1 = 9a
⇒ a2 + 1 = 9 a ⇒ a + 1 = 9 a
On squaring both sides,a2 + 1 + 2 = 81 a2 ⇒ a2 + 1 = 81 – 2 = 79 a2
-
If a2 = b2 = c2 = 1 then 1 + 1 + 1 is b + c c + a a + b 1 + a 1 + b 1 + c
-
View Hint View Answer Discuss in Forum
a2 = b2 = c2 = 1 b + c c + a a + b ⇒ a2 = 1 b + c
⇒ a2 = b + c
⇒ a2 + a = a + b + c
⇒ a (a + 1) = a + b + c⇒ 1 = a a + 1 a + b + c ⇒ b2 = 1 ⇒ b2 = c + a a + 1
⇒ b2 + b = a + b + c
⇒ b (b + 1) = a + b + c⇒ 1 = b b + 1 a + b + c and c2 = 1 ⇒ c2 = a + b a + b
⇒ c2 + c = a + b + c
⇒ c (c + 1) = a + b + c⇒ 1 = c c + 1 a + b + c ∴ 1 + 1 + 1 1 + a 1 + b 1 + c ∴ a + b + b a + b + c a + b + c a + b + c = a + b + c = 1 a + b + c Correct Option: A
a2 = b2 = c2 = 1 b + c c + a a + b ⇒ a2 = 1 b + c
⇒ a2 = b + c
⇒ a2 + a = a + b + c
⇒ a (a + 1) = a + b + c⇒ 1 = a a + 1 a + b + c ⇒ b2 = 1 ⇒ b2 = c + a a + 1
⇒ b2 + b = a + b + c
⇒ b (b + 1) = a + b + c⇒ 1 = b b + 1 a + b + c and c2 = 1 ⇒ c2 = a + b a + b
⇒ c2 + c = a + b + c
⇒ c (c + 1) = a + b + c⇒ 1 = c c + 1 a + b + c ∴ 1 + 1 + 1 1 + a 1 + b 1 + c ∴ a + b + b a + b + c a + b + c a + b + c = a + b + c = 1 a + b + c